Isolation and Characterization of Two Novel Genera of Jumbo Bacteriophages Infecting Xanthomonas vesicatoria Isolated from Agricultural Regions in Mexico - Claudia Villicaña; Lucía M. Rubí-Rangel; Luis Amarillas; Luis Alberto Lightbourn-Rojas; José Armando Carrillo-Fasio; Josefina León-Félix (Antibiotics, 2024)
Bacterial spot is a serious disease caused by several species of Xanthomonas affecting pepper and tomato production worldwide. Since the strategies employed for disease management have been inefficient and pose a threat for environmental and human health, the development of alternative methods is gaining relevance. The aim of this study is to isolate and characterize lytic phages against Xanthomonas pathogens. Here, we isolate two jumbo phages, named XaC1 and XbC2, from water obtained from agricultural irrigation channels by the enrichment technique using X. vesicatoria as a host. We determined that both phages were specific for inducing the lysis of X. vesicatoria strains, but not of other xanthomonads. The XaC1 and XbC2 phages showed a myovirus morphology and were classified as jumbo phages due to their genomes being larger than 200 kb. Phylogenetic and comparative analysis suggests that XaC1 and XbC2 represent both different and novel genera of phages, where XaC1 possesses a low similarity to other phage genomes reported before. Finally, XaC1 and XbC2 exhibited thermal stability up to 45 °C and pH stability from 5 to 9. All these results indicate that the isolated phages are promising candidates for the development of formulations against bacterial spot, although further characterization is required.